Peripheral Tissue Homing Receptor Control of Naïve, Effector, and Memory CD8 T Cell Localization in Lymphoid and Non-Lymphoid Tissues - Brinkman, C. C.; Peske, J. D.; Engelhard, Victor H. (Frontiers in Immunology, 2013)
T cell activation induces homing receptors that bind ligands on peripheral tissue vasculature, programming movement to sites of infection and injury. There are 3 major types of CD8 effector T cells based on homing receptor expression, which arise in distinct lymphoid organs. Recent publications indicate that naïve, effector, and memory T cell migration is more complex than once thought; while many effectors enter peripheral tissues, some re-enter lymph nodes and contain central memory precursors. Lymph node re-entry can depend on CD62L or peripheral tissue homing receptors. Memory T cells in lymph nodes tend to express the same homing receptors as their forebears, but often are CD62Lneg. Homing receptors also control CD8 T cell tumor entry. Tumor vasculature has low levels of many peripheral tissue homing receptor ligands, but portions of it resemble high endothelial venules, enabling naïve T cell entry, activation and subsequent effector activity. This vasculature is associated with positive prognoses in humans, suggesting it may sustain ongoing anti-tumor responses. These findings reveal new roles for homing receptors expressed by naïve, effector and memory CD8 T cells in controlling entry into lymphoid and non-lymphoid tissues.